Environmental Impact Assessment on Rural Water Supply Scheme Under Jal Jeevan Mission. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Jal Jeevan Mission (JJM), launched by the Government of India in 2019, aims to provide safe and adequate drinking water through Functional Household Tap Connections (FHTC) to all rural households. This research paper evaluates the environmental impacts of rural water supply schemes implemented under JJM. The study analyzes positive impacts such as improved water quality, reduction in waterborne diseases, and sustainable water management, as well as potential environmental challenges including groundwater depletion and infrastructure-related ecological disturbances. The findings suggest that while JJM significantly improves rural living standards, proper environmental management and sustainable water resource planning are essential for long-term success.